(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2007)
Relationships between the traits associated with lodging resistance in wheat were studied within the period of 1999-2002 at Wheat Research Center, Dinajpur in both F1 and F2 generations of a 9 × 9 diallel cross without reciprocal. The genotypic and phenotypic correlation coefficients studied in F1 and F2 generations were similar with some exceptions. In both F1 and F2 generation, the second internode breaking strength was positively correlated with diameter, wall thickness and unit-stem weight of second internode, and main shoot weight but negatively with plant height and second internode length at both genotypic and phenotypic levels. It was observed from path coefficient analysis in both F1 and F2 generations that the second internode unit-stem weight had high positive direct effect on its breaking strength. Main shoot weight, second internode diameter and wall thickness positively influenced breaking strength through its unit-stem weight. Simultaneous selection for the traits contributing to lodging resistant in semi-dwarf wheat might be effective in the improvement of lodging resistance in bread wheat. DOI: http://dx.doi.org/10.3329/bjpbg.v20i2.17036